O-GlcNAc Modification During Pregnancy: Focus on Placental Environment - Lima, Victor Vitorino; Dela Justina, Vanessa; dos Passos, Rinaldo Rodrigues; Volpato, Gustavo Tadeu; Souto, Paula Cristina S.; San Martin, Sebastian; Giachini, Fernanda Regina (Frontiers in Physiology, 2018)
Successful placentation is a key event to allow fetal development, which starts after embryo implantation into the uterine wall, eliciting decidualization, placentation and remodeling of blood vessels to provide physiological exchanges between embryo-fetus and mother. Several signaling pathways are recruited to modulate such important process and specific proteins that regulate placental function are target for the glycosylation with O-linked β-N-acetylglucosamine (O-GlcNAc) or O-GlcNAcylation. This is a reversible posttranslational modification on nuclear and cytoplasmic proteins, mainly controlled by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). O-GlcNAcylation has been implicated as a modulator of proteins both in physiological and pathological conditions and more recently, O-GlcNAc was shown to be an important modulator in placental tissue. On this mini-review article, the interplay between O-GlcNAcylation of proteins and placental function will be addressed, discussing possible implications of this posttranslational modification through placental develop and pregnancy.